Critical Knowledge and the Neoliberal University. Reflections in the Light of the Work of C. W. Mills, Olùfémi O. Tàíwò, Kevin Ochieng Okoth, and the Positional Sociology - Galiano, Angelo (PARTECIPAZIONE E CONFLITTO, 2025)
This article offers a critical reflection on the role of the social science scholar within the neoliberal university, interrogating the epistemic, institutional, and political constraints currently shaping the production of knowledge. Drawing on C. Wright Mills’s The Sociological Imagination, the paper engages with three further key contributions: Olùfémi O. Tàíwò’s Elite Capture, Kevin Ochieng Okoth’s Red Africa, and the collective volume Sociologia di posizione by de Nardis, Petrillo, and Simone. These works provide a conceptual framework for analysing the processes through which critical knowledge is co-opted, depoliticised, or rendered ineffectual. The article focuses on two prevailing dynamics: the hegemony of managerial rationality, which subordinates research to metrics of productivity and competitiveness; and the proliferation of symbolic forms of critique devoid of substantive political impact. In response, the paper explores the possibility of reclaiming the scholar’s role as a situated and responsible actor, capable of reconnecting knowledge production with broader social struggles. The experience of the Italian network Sociologia di posizione is presented as a concrete attempt to collectively organise epistemic and material resistance, and to restore a public, transformative function to the social sciences.